Partnerstwo publiczno-prywatne w rozwoju lokalnym i regionalnym Szansa czy zagrożenie? - Wasiak, Andrzej (Public-Private Partnership in Local and Regional Development : An Opportunity or a Threat?, 2007)
The article contains synthetic comments that relate to the theoretical basis of a partnership between the public and the private. It presents selected examples of such co-operation taking place at both the local and the regional level, while indicating a possibility of a threat to public interest, but also a possibility of a rational and effective co-operation between public and private entities, as can be learned from the experience of other states. This can be used to facilitate local and regional development through carrying out mutual enterprises in the form of the public private partnership.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 131-140